2018
DOI: 10.1038/s41598-018-22429-z
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Race are both Independently associated with Increased Hospitalization Rate among Crohn’s Disease Patients

Abstract: Racial disparities are observed clinically in Crohn’s Disease (CD) with research suggesting African Americans (AA) have worse outcomes than Caucasian Americans (CA). The aim of this study is to assess whether socioeconomic status (SES) rather than race is the major predictor of worse outcomes. We designed a retrospective cohort study of 944 CD patients seen at our center. Patients’ billing zip codes were collected and average income and percent of population living above or below poverty level (PL) for each zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Disparate outcomes have also been noted in hospitalizations, length of stay and readmissions. A single-centre retrospective study assessed rates of Crohn's disease hospitalizations by race and ethnicity and found hospitalizations were four times higher for those in the lowest income group compared with the highest income group on unadjusted analysis, and twice as high in an adjusted analysis [27]. In addition, Black patients in the study were twice as likely to have a Crohn's disease related hospitalization in comparison to white patients, illustrating the separate yet distinct disparities due to poverty and race/racism.…”
Section: Healthcare Utilizationmentioning
confidence: 99%
“…Disparate outcomes have also been noted in hospitalizations, length of stay and readmissions. A single-centre retrospective study assessed rates of Crohn's disease hospitalizations by race and ethnicity and found hospitalizations were four times higher for those in the lowest income group compared with the highest income group on unadjusted analysis, and twice as high in an adjusted analysis [27]. In addition, Black patients in the study were twice as likely to have a Crohn's disease related hospitalization in comparison to white patients, illustrating the separate yet distinct disparities due to poverty and race/racism.…”
Section: Healthcare Utilizationmentioning
confidence: 99%
“…Lower-income levels were associated with higher hospitalization rate. In a retrospective analysis of CD patients, the incidence rate for hospitalization for lowest-income group was 118 per 100-person years (CI 91.4-152.3) and for the highest-income group was 29 (CI 21.7-38.9) [40]. In CD, smoking has also been shown to increase the risk of hospitalization [41].…”
Section: Robin Dalal and David Schwartzmentioning
confidence: 99%
“…[ 3,9–11 ] This spans the gamut of age, sex, race, socioeconomic conditions, and geographic locale and translates into $6–15 billion in direct healthcare costs in the United States. [ 3,12,13 ]…”
Section: Introductionmentioning
confidence: 99%